"Apostle to the Disillusioned" - A Response to Thomas Albert Howard - Halík, Tomáš (Christian scholar's review, 2024)
The Afternoon of Christianity: The Courage to Change Tomáš Halík Published by University of Notre Dame Press in 2024 290pp/$ 25.00 / 9780268207465